1987
DOI: 10.1302/0301-620x.69b1.3818743
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondritis dissecans of the ankle. A 20-year follow-up study

Abstract: Thirty patients with osteochondritis dissecans of the ankle have been followed up for an average of 21 years. The histories and radiographs were revi#{231}wed, and it was found that most patients had only minor radiographic changes and symptoms. Two patients had developed osteoarthritis but in only one was this severe Osteochondritis dissecans in the ankle thus seems to differ from the same lesion in the knee where late osteoarthritis often occurs. Two lesions were located on the joint surface of the distal ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
88
3
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(94 citation statements)
references
References 13 publications
2
88
3
1
Order By: Relevance
“…2,7,12,15,18 The natural history of OLTs is not well described. It is unclear whether these lesions tend to progress in terms of size and symptoms or lead to joint deterioration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,7,12,15,18 The natural history of OLTs is not well described. It is unclear whether these lesions tend to progress in terms of size and symptoms or lead to joint deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear whether these lesions tend to progress in terms of size and symptoms or lead to joint deterioration. [2][3][4]9,12,[17][18][19] The purpose of this study was to describe the natural history of OLTs in a cohort of patients treated nonoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…18 No patients who were diagnosed with OCD of the talus during childhood developed osteoarthritis. 18 Management of juvenile OCD of the talus remains controversial. Earlier studies recommend conservative management, whereas more recent studies advocate surgical management when 6 months of conservative management fails.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The lesions are classified into four stages: stage I, a small area of compression of subchondral bone; stage II, a partially detached osteochondral fragment; stage III, a completely detached fragment which remains in the talar crater; and stage IV, displacement of the fragment. We have shown that arthroscopic drilling is appropriate for young patients with an early stable lesion.…”
mentioning
confidence: 99%